Estimating CO2 emissions due to present and future suborbital space tourism industry. - Angela M Huang; Yangyang Xu (PLoS ONE)
Estimating and predicting CO2 emissions are the keys to achieving the overall greenhouse gas emission goals for 2030 and 2050. Recent surges in space tourism have generated significant interest and concern. However, the associated CO2 emission and potential future increase remain largely uncertain due to limited publicly available information from the industry. Focusing on suborbital flights, we develop an analytical model to estimate the associated CO2 emissions, considering differences in spacecraft, fuel types, and flight characteristics. The model is based on basic physical principles and fundamental kinetics of the launching and landing phases. We find that suborbital tourism releases 400-1,000 times more CO2 per passenger per hour compared with commercial aviation flights. The spacecraft using liquid hydrogen as fuel releases nearly the least amount of CO2; however, it is still associated with 90-106 metric tons of indirect CO2 emissions due to the fuel production process. In contrast, spacecraft using kerosene (RP-1) and solid fuel (HTPB), respectively, release significantly more. However, if methane (natural gas) is used as fuel, its emissions may become comparable with those using liquid hydrogen, but its maximum reduction in emission can only be less than 10% because that is the amount associated with production. Generally, conventional rocket fuels generate more CO2 than emerging fuels such as hydrogen and methane. Even though the total emissions of suborbital flights are still small compared with commercial aviation, their emission intensity (i.e., per passenger per hour) is enormous (85-226 tons vs. 250 kg). If the demand for suborbital flights increases significantly, as some have speculated, the total annual emission can be as large as 21 Mt CO2 per year in a decade, which exceeds the annual emission of more than 100 countries. Even adopting a conservative estimate, CO2 emissions for suborbital travel can grow to a similar size to that of Congo (with a population of nearly 100 million). Therefore, the CO2 emission from emerging suborbital travel needs more attention in the future.